Traffic optimization at the Application Level Proof of Concept, development and usefulness evaluation of the ALTO solution - Camaz, Gonçalo (2020)
This paper presents an overview, proof of concept, and a preliminary demonstrative benchmarking study of the Application-Layer Traffic Optimization (ALTO) architecture proposed by the IETF ALTO Working Group. The main ALTO system purpose is to allow applications to get a more complete view of the underlying network infrastructure, allowing for wellreasoned connection decisions in situations of service redundancy. This paper first begins with a technical description of the ALTO project, and afterwards evaluates how P2P applications, guided by our proposed prototype implementation of the ALTO architecture, perform in comparison to traditional peer selection algorithms on the task of downloading a file in a typical file-sharing P2P network environment. The obtained results from our developed ALTO prototype system state that an application guided by the ALTO solution reduced overall network usage by around 40% with no significant impact in the application performance.